2019
DOI: 10.2174/1381612825666190709205028
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines: A Potential Therapeutic Target to Suppress Autoimmune Arthritis

Abstract: Background:: Chemokines are a family of low molecular weight proteins that induce chemotaxis of inflammatory cells, which mainly depends on the recognition of a chemo-attractant gradient and interaction with the substratum. In Rheumatoid Arthritis (RA), abundant chemokines are expressed in synovial tissue, cause inflammatory cells migration into the inflamed joint that necessitates the formation of new blood vessels i.e. angiogenesis. Over the decades, studies showed that continuous inflammation may lead to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…In general, C-glycosyl flavonoids exhibit more potent activity compared with that mediated by their corresponding O-glycosyl flavonoid and aglycone counterparts ( 23 ). Previous studies have shown that treatment with flavonoid C-glycosides are associated with a number of health benefits in the prevention and management of diseases such as cancer, diabetes, and cardiovascular disease ( 23 ), especially when used as a treatment for antigen-induced arthritis ( 24 , 25 ). However, the underlying mechanism of the effects of vicenin 3 on articular cartilage degeneration during OA remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In general, C-glycosyl flavonoids exhibit more potent activity compared with that mediated by their corresponding O-glycosyl flavonoid and aglycone counterparts ( 23 ). Previous studies have shown that treatment with flavonoid C-glycosides are associated with a number of health benefits in the prevention and management of diseases such as cancer, diabetes, and cardiovascular disease ( 23 ), especially when used as a treatment for antigen-induced arthritis ( 24 , 25 ). However, the underlying mechanism of the effects of vicenin 3 on articular cartilage degeneration during OA remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%